Implementation of wireless sensor network in oil and gas specifically for personnel positioning application - Mazlan, M.A.A.A. (Institute of Electrical and Electronics Engineers Inc., 2015)
The invention of WSN-based indoor positioning is to design effective personnel positioning system, monitor the personnel movement in oil and gas platform and alert the personnel if they entered a restricted area. Personnel tracking system in hazardous working environment such as in oil gas platform is very crucial due to GPS incapability inside a concrete building structure. Real-time monitoring of personnel health and condition is a top priority for immediate response in emergency situation. Communication device limitation in oil and gas platform will be hard for the supervisor to inform the personnel for an emergency evacuation. Personnel position application using WSN is determined based on RSSI values of multiple XBee multipoint RF modules consist of personnel node, fixed nodes and server node. A positioning algorithm will be used for the estimation of personnel location in the oil and gas platform. Sectioning method using XBee IEEE 802.15.4 as a WSN is proposed for personnel positioning application. Â© 2015 IEEE.